The impact of COVID-19 on the assessment and management of ectopic pregnancies - Bethany Chung; Charlotte Greene; Alice Pearson; Lisa M Starrs; W Colin Duncan (Bioscientifica, 2023)
During the COVID-19 pandemic, the public delayed seeking medical help, which may have affected the impact of having an ectopic pregnancy. An ectopic pregnancy is when pregnancy tissue grows outside its normal position in the womb, and it can be life-threatening. It can be treated by non-surgical or surgical options, and any delay in seeking help can reduce the options for treatment and increase the need for more urgent management. We wanted to assess whether there were differences in the presentation and management of ectopic pregnancies in a major teaching hospital between 2019 (pre-COVID-19) and 2021 (COVID-19 period). We found that the pandemic did not cause a delay in seeking medical help or cause worse outcomes. In fact, immediate surgical treatment and time in the hospital were less during COVID-19, perhaps because of a desire to avoid admission to hospital. One outcome of COVID-19 is reassurance that we can safely use more non-surgical treatments for ectopic pregnancies.